1999
DOI: 10.1063/1.124848
|View full text |Cite
|
Sign up to set email alerts
|

Band gap and wave guiding effect in a quasiperiodic photonic crystal

Abstract: A two-dimensional octagonal quasiperiodic photonic crystal composed of alumina cylinders is prepared. The transmission spectra of the quasicrystal are measured in the microwave region for the TM wave. We find that the position and width of the band gap do not depend on the incident direction, while the band structure can appear for quite a small piece of the quasicrystal. Two types of waveguide, a straight guide and a bending guide with two sharp 90° corners, are fabricated by removing three rows of cylinders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(92 citation statements)
references
References 12 publications
0
92
0
Order By: Relevance
“…[5][6][7][8] Various wave phenomena that depend on the existence of band gaps, such as defects and waveguides, have also been extensively studied. [11][12][13][14][15] Recently, a wide interest has been attracted to the bandedge states in quasiperiodic composites. 4,[16][17][18][19][20][21][22][23] Firstly, the property of wave functions at band edges in quasiperiodic structures remains an interesting and unresolved topic.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Various wave phenomena that depend on the existence of band gaps, such as defects and waveguides, have also been extensively studied. [11][12][13][14][15] Recently, a wide interest has been attracted to the bandedge states in quasiperiodic composites. 4,[16][17][18][19][20][21][22][23] Firstly, the property of wave functions at band edges in quasiperiodic structures remains an interesting and unresolved topic.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies on quasiperiodic PCs, the ratio was larger than 8.9. [7,8,9,10,11,13] Exceptions are the results of 12-fold symmetric quasiperiodic PCs, which have complete PBGs even when the ratio is 2.1. [12,13] Our study has shown that complete PBGs exist in Penrose and octagonal PCs with a small ratio of dielectric constants (2.4), suggesting that any quasiperiodic PC can have a PBG in optimum choice of r/a even when the ratio is as small as 2.4.…”
Section: Isotropic Photonic Band Gapmentioning
confidence: 99%
“…The quasiperiodic PC consists of rods placed perpendicular to the basal plane on vertices of tiles composing a quasiperiodic pattern. Complete PBGs have been observed in 5-fold (Penrose pattern), [7] 8-fold (octagonal pattern), [8,9,10] 10-fold, [11] and 12-fold [11,12,13] symmetric quasiperiodic PCs. An important feature is that the position and width of the PBG are almost independent of the incident angle of the light.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some interesting review articles on photonic quasicrystals can be found in the literature [11,12]. It has been demonstrated that photonic quasicrystals can also exhibit photonic band gaps [13][14][15]. These aperiodic structures can be generated by deterministic rules and posses long-range order [16].…”
Section: Introductionmentioning
confidence: 99%